Microbiological surveillance in reducing potential infection risk. (30th September 2020) - Tuvo, B; Cristina, M L; Spagnolo, A M; Totaro, M; Baggiani, A; Privitera, G; Casini, B
Abstract: Background: Failure in reprocessing of endoscopes has been reported as one of the top ten most important threats to patient health. Materials/Methods: The study was conducted in two digestive endoscopy centres of a teaching hospital (29, 000 endoscopies/year, of which 550 endoscopic retrograde cholangiopancreatography (ERCP). Following two cases of bacteremia due to KPC-producing Klebsiella pneumoniae temporally related to ERCP and 89% of non-compliance detected on endoscopes subjected to microbiological surveillance, the reprocessing activities were audited and implemented to ensure guideline compliance. Clinical and microbiological surveillance were reinforced and all responsibilities for each phase identified according to UNI/TR11662. Microbiological surveillance was performed according to the 'Duodenoscope Surveillance Sampling and Culturing Protocols' protocol, CDC, 2018. Results: In the 11 months of surveillance, 47 endoscopes were sampled (13 colonoscopes, 9 gastroscopes, 23 duodenoscopes and 2 echoendoscopes), 19 washer-disinfector machines and 9 medical cabinets. 36% (17/47) of endoscope internal channels resulted non-compliant, 17% (4/23) in duodenoscopes. NDM-producing K. pneumoniae was isolated in 2 gastroscopes always associated with the use on a colonized patient. The inlet and final rinsing water of washer-disinfectors and medical cabinets resulted always conformed. Non-conformities were managed immediately in order to avoid infectious risks for patients. Conclusions: Microbiological surveillance of endoscopes after reprocessing allowed to prevent infections in patients undergoing endoscopic procedures. Key messages: Training of health workers followed by strict adherence to guidelines is the most appropriate tool in preventing and controlling infections related to the use of endoscopes. Endoscopy and reprocessing staff should follow a formal recognized endoscopy reprocessing training program, followed by regular practice and periodically updated training to maintain competency.